Eyewitness: Mammal - Thomson, Richard; Steiner, Ben.; Foulkes, Jerry; Butt, Bill.; Kamei, Mike.; Sheen, Martin; Dagul, Guy.; Michelmore, Guy.; Parker, Steve, 1952-; Dorling Kindersley Vision; BBC Worldwide Americas, Inc. ([New York, N.Y.] : DK Publishing, 2007)
Reveals the most amazing facts and folklore about our favorite furry animals. Towering or tiny, ferocious or friendly, mammals trot, hop, swim, and soar. Meet the creatures that make up this huge and varied family.
Eyewitness mammal (1996) (ca. 35 min.) -- The making of Eyewitness (1994) (ca. 25 min.) / written and produced by Bill Butt ; director/cameraman, Mike Kamei -- Discover more about DK Eyewitness (ca. 2 min.)
Music, Guy Dagul (1st work), Guy Michelmore (2nd work).
Narrator: Martin Sheen.
Originally released for television broadcast in 1996; 1st work c1996; 2nd work c1994.
DVD, all regions, full screen (1.33:1) presentation; Dolby Digital.
Keywords: Mammals; Mammals -- Behavior; Animal intelligence; Mammals -- Folklore; Educational films